2017
DOI: 10.1111/ijfs.13448
|View full text |Cite
|
Sign up to set email alerts
|

Identification of angiotensin converting enzyme inhibitory and antioxidant peptides in a whey protein concentrate hydrolysate produced at semi‐pilot scale

Abstract: Summary Antioxidant and angiotensin converting enzyme (ACE) inhibitory peptides were identified in a 5 kDa ultrafiltration permeate of a whey protein hydrolysate generated at semi‐pilot scale. Further laboratory scale ultrafiltration of this 5 kDa permeate resulted in a 0.65 kDa permeate with antioxidant, (1.11 ± 0.074 μmol TE per mg dry weight, oxygen radical absorbance capacity, ORAC) and ACE inhibitory (ACE IC50 0.215 ± 0.043 mg mL−1) activities. Semi‐preparative (SP) reverse phase high‐performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 42 publications
3
13
0
1
Order By: Relevance
“…Previously, β-LG peptides f(15-18) VAGT, f(24-26) MAA and f(71-74) IIAE inhibited peroxyl radicals, using the oxygen reactive absorbance capacity (ORAC) assay with values between 0.33 and 1.79 μmol trolox equivalents (TE)/mmol peptide (O'Keeffe, Conesa & FitzGerald, 2017). Of these, our study revealed that the peptides VAGT and IIAE were able to pass through the intestinal co-culture.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, β-LG peptides f(15-18) VAGT, f(24-26) MAA and f(71-74) IIAE inhibited peroxyl radicals, using the oxygen reactive absorbance capacity (ORAC) assay with values between 0.33 and 1.79 μmol trolox equivalents (TE)/mmol peptide (O'Keeffe, Conesa & FitzGerald, 2017). Of these, our study revealed that the peptides VAGT and IIAE were able to pass through the intestinal co-culture.…”
Section: Discussionmentioning
confidence: 72%
“…Of all these bioactivities, ACE inhibition and antioxidant activity are extensively studied, but mainly on a separate basis. For instance, Guo, Pan and Tanokura [9] and O'keeffe, Conesa and FitzGerald [16] reported ACE inhibition between 40.0-84.4% for different whey products while Ajlouni and Pan [17] as well as Zhang et al [18] reported antioxidant activities between 0.0-72.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…O'keeffe et al . () identified five antioxidant peptides from 0.65 kDa permeate of milk protein hydrolysates that matched the sequences of a s1 ‐casein and β‐lactoglobulin.…”
Section: Resultsmentioning
confidence: 93%